Effect Of Baby Spa On Sleep Quality of Baby 3-6 Months - Anisa Oktapiani; Siti Patimah; Etin Rohmatin (Midwifery and Nursing Research, 2020)
Background: Infancy was a golden period for children's growth and development, so it needs special attention. One of the factors that influence a baby's growth and development was sleep and rest. If the baby's sleep was disrupted then the child's physical growth will be disrupted, the cognitive and emotional development of the baby will be disrupted and this will affect the development of the brain and the potential that should develop will be lost. Baby spa was one of the useful non-pharmacological therapies which was to increase the concentration of the baby and make the baby sleep well. The aim of this study was to determine the effect of Baby Spa on sleep quality of infants 3-6 months.Methods: The design of this research was pre-experimental, one group pretest-post use a brief infant sleep questionnaire (BISQ). The sampling technique was purposive sampling with a sample of 31 infants. Statistical analysis used wilcoxon signed rank test.Results: Results of studies that had been carried out obtained frequency of sleep quality is p=0,001. That suggests baby spa were effective for improving sleep quality.Conclusion: Baby SPA was effective for improving the quality of sleep for infants 3-6 months. for mothers who had babies to add insight about the Baby Spa, because Baby Spa had many benefits, including regular sleep patterns